Communication Strategy Of Bank Indonesia's Mentoring Program For Partnered Msmes (A Qualitative Descriptive Study On Kaywood MSME) - Saputra, Andika; Kurniawati, Nia Kania; Widyastuti, Nurprapti Wahyu (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Every business actor expects their products to be recognized by the wider community, basically consumers will buy a well-known brand because they feel safe with something that is already known. People can distinguish products from each other by looking at the logo, shape and image, called brand awareness. The marketing communication strategy used by Kaywood Watches to attract buyers lies in its innovative, artistic and trendy design, which is also very suitable for use in special events and can be used as gifts, and is made of ebony wood, sonokeling, teak wood and maple wood. This research focuses on the Communication Strategy of Bank Indonesia's Assistance Program for Fostered MSMEs. The theory used to analyze is SWOT Analysis. This research uses a descriptive research method, where the researcher not only describes or explains the problems researched according to the facts, but is also supported by questions by conducting direct interviews about the object of the research, namely Kaywood's marketing communication strategy through social media in building Brand Awareness. Then, the data can be collected, compiled, explained, and analyzed accompanied by problem solving or solutions according to the problem being researched. The findings for the Communication Strategy of Bank Indonesia's Assistance Program for Fostered MSMEs are by providing product assistance by providing names and logos Institutional strengthening in the form of providing opportunities to participate in marketing events and exhibitions, as well as expanding cooperation with external parties. Technical assistance is in the form of providing training, research and facilities to fostered MSMEs. Financing is in the form of providing working capital loan assistance to fostered MSMEs that can be used to purchase machinery and raw materials. The social media used by Kaywood is digital marketing through Facebook, Instagram, TikTok, Youtube, Shopee and Blibli as well as Lazada.